2019
DOI: 10.1002/anie.201813305
|View full text |Cite
|
Sign up to set email alerts
|

Interconverting Lanthanum Hydride and Borohydride Catalysts for C=O Reduction and C−O Bond Cleavage

Abstract: Theauthors declare no conflict of interest.Keywords: CÀObond cleavage ·h omogeneous catalysis · hydroboration ·lanthanum hydride ·s aturation kinetics Scheme 3. (A) First-order dependence on [ester] indicates CÀOb ond cleavage occurs after the turnover-limiting step, whereas (B) half-order dependence on ester indicates CÀObond cleavage happensp rior to or during the turnover limiting step.Scheme 4. Mechanisms for 1-catalyzed hydroboration of esters. Mechanisms A and B are both consistent with kinetic experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“… [12b] Catalytic hydroborations of carboxylates have recently been reported with transition metal catalysts, [13] bulky organo‐magnesium,[ 14 , 15 ] amidomagnesium,[ 7a , 16 ] and rare earth metal catalysts. [ 7d , 7e , 17 , 18 ] Catalytic Mn(hmds) 2 enabled clean ester reduction with HBpin at room temperature (Scheme 3 , center). Alkanoates and benzoates were reactive; halides, CF 3 , and heteroaryl substituents were tolerated.…”
Section: Resultsmentioning
confidence: 99%
“… [12b] Catalytic hydroborations of carboxylates have recently been reported with transition metal catalysts, [13] bulky organo‐magnesium,[ 14 , 15 ] amidomagnesium,[ 7a , 16 ] and rare earth metal catalysts. [ 7d , 7e , 17 , 18 ] Catalytic Mn(hmds) 2 enabled clean ester reduction with HBpin at room temperature (Scheme 3 , center). Alkanoates and benzoates were reactive; halides, CF 3 , and heteroaryl substituents were tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…( S )‐(+)‐2‐Methyl butyronitrile was reduced at 50 °C to the β‐chiral butylamine in near‐quantitative yield (a58921 =6.2°, CH 3 OH) [12b] . Catalytic hydroborations of carboxylates have recently been reported with transition metal catalysts, [13] bulky organo‐magnesium, [14, 15] amidomagnesium, [7a, 16] and rare earth metal catalysts [7d–e, 17, 18] . Catalytic Mn(hmds) 2 enabled clean ester reduction with HBpin at room temperature (Scheme 3, center).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the Sadow group developed organolanthanum complexes immobilized on the surface of mesoporous silica nanoparticles, La[C(SiHMe 2 ) 2 ] n @MSN 700 ( 20a ) (Figure 4) and La[C(SiHMe 2 ) 2 ] n @MSN 550 ( 20b ), which significantly inhibited the migration of phenyl group in the hydroboration of stilbene oxides, giving sole product (Scheme 19). [ 33 ] Compared with the former homogenous catalysis, the solid‐supported catalyst exhibited equivalent capability and even better activity and regioselectivity in the case of styrene oxides and stilbene oxides, and more importantly, the latter could be reused for 3 cycles without compromising the performance. However, the mechanism of ring‐opening of epoxides is still not clear, although the authors believed that LaH 2 Bpin species should be responsible for the transformation (Scheme 20).…”
Section: Hydroboration Of C–hetero Unsaturated Bonds: Aldehydes Keton...mentioning
confidence: 99%
“…Indeed, esters could undergo the transformation smoothly promoted by the lanthanum complex La[C (SiHMe 2 ) 2 ] 3 (18) (Figure 4) under mild conditions, albeit subsequent studies showed La-H is not competent to the transformation (Scheme 14). [33] With only 0.01 mol% catalyst loading, ethyl acetate could be quantitatively converted into corresponding borate ester within 2 h at room temperature. A broad scope of functional groups was tolerated in the conditions, and unsaturated C-C double bonds were left intact.…”
Section: Esters and Epoxidesmentioning
confidence: 99%
See 1 more Smart Citation